Financial Accounting Module Configuration Plan for Enterprise Resource Planning (ERP) System in a State University in Region 2, Philippines - Bartolome, Laarnie O. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – This paper showcased the benefits and impact of SAP-ERP for Higher Education. Specifically, it answered the questions: What are the configuration requirements for organizational structure; processes; and master data? What are issues related to ERP implementation? What ICT infrastructure shall support the implementation? Method – This study utilized the Accelerated System Applications and Products (ASAP) methodology that provided a roadmap for optimizing the implementation of SAP-ERP systems. This was developed to guarantee a cost-effective and on-time delivery of all projects.   Results – For the Organizational Structure, Processes, and Master Data, SAP ERP increased efficiency and sped up the operation of all the funds of the organization. Staff could perform the transaction and generate reports efficiently. The financial heads view reports in a fast presentation. The issues and challenges included the high cost of ERP software, configuration, and training. Migration to an ERP system might be hard due to the manual operation and adequate time to convert old data into the new system. The minimum hardware and software requirements were met by the current ICT infrastructure. Conclusion –The institution with its ability to provide solutions to needs was able also to fund the implementation cost. The minimum requirements in the implementation were met by the organization’s ICT infrastructure. Thus, SAP ERP implementation was possible. Recommendations –It is recommended that SAP ERP will be implemented in the university to be more competitive and gain an advantage in pursuing its vision.  For maximum use of an integrated system, the institution may also consider other SAP ERP modules such as M, HR, SD, and the like. Research Implications – The Institution may adopt ERP because it is the most important business technology that penetrates commerce, industries, and educational institutions focusing on standardization and synchronization of information to improve efficiency and output, especially on financial matters.